Aldosterone stimulates the cardiac sodium/bicarbonate cotransporter via activation of the g protein-coupled receptor gpr30 - de Giusti, Verónica Celeste (2015)
Some cardiac non-genomic effects of aldosterone (Ald) are reported to be mediated through activation of the classic mineralocorticoid receptor (MR). However, in the last years, it was proposed that activation of the novel G protein-coupled receptor GPR30 mediates certain non-genomic effects of Ald. The aim of this study was to elucidate if the sodium/bicarbonate cotransporter (NBC) is stimulated by Ald and if the activation of GPR30 mediates this effect. NBC activity was evaluated in rat cardiomyocytes perfused with HCO3-/CO2 solution in the continuous presence of HOE642 (sodium/hydrogen exchanger blocker) during recovery from acidosis using intracellular fluorescence measurements. Ald enhanced NBC activity (% of δJHCO3-; control: 100±5.82%, n=7 vs Ald: 151.88±11.02%, n=5; P<0.05), which was prevented by G15 (GPR30 blocker, 90.53±7.81%, n=7). Further evidence for the involvement of GPR30 was provided by G1 (GPR30 agonist), which stimulated NBC (185.13±18.28%, n=6; P<0.05) and this effect was abrogated by G15 (124.19±10.96%, n=5). Ald- and G1-induced NBC stimulation was abolished by the reactive oxygen species (ROS) scavenger MPG and by the NADPH oxidase inhibitor apocynin. In addition, G15 prevented Ald- and G1-induced ROS production. Pre-incubation of myocytes with wortmannin (PI3K-AKT pathway blocker) prevented Ald- or G1-induced NBC stimulation. In summary, Ald stimulates NBC by GPR30 activation, ROS production and AKT stimulation.